Current Challenges and Future Potentials of Social Economy in Croatia - Babić, Zdenko; Baturina, Danijel (Calitatea Vieții, 2020)
The social economy sector in Croatia has been neglected for a long time and has not been recognized as a space for sustainable jobs and the development of a more inclusive and cohesive society, as is the case in many Eastern and Central European countries. On the other hand, social entrepreneurship is a relatively new phenomenon established in this century. The aim of this paper is to assess the trends and challenges of social economy development in Croatia as the newest, last EU member state. On the basis of a secondary data analysis, the paper scrutinizes trends in social economy development. Social entrepreneurship is analysed as a part of the social economy that is strengthening, as well as the economic activity of associations that tends to turn into a social economy or a solidarity economy. The paper will also give an overview of the instances of the institutional context of the development of cooperatives and social enterprises, such as the recent legislative and policy changes, as well as the institutional framework with some insights into recommendations how to promote the development of the social economy sector in Croatia.